2001
DOI: 10.1001/archinte.161.6.859
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Methicillin-Resistant Staphylococcus aureus From a Health Center Ward and Associated Nursing Home

Abstract: It is possible to eradicate MRSA from a long-term health care facility even after 13 cases by applying strict control measures. Our experience may be valuable in the future decision-making process for control of new and more challenging multiresistant bacteria, eg, vancomycin-resistant strains of MRSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
60
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 23 publications
1
60
0
1
Order By: Relevance
“…Mupirocin calcium ointment is a topical antibiotic indicated for the eradication of nasal carriage of staphylococci, including methicillin-resistant strains. Mupirocin alone or in combination with other antimicrobial agents decreases S. aureus colonization among residents of LTCFs (3,7,8,20). Several outbreaks of methicillin-resistant S. aureus colonization and infection in LTCFs have been reported, and until now, it was thought that the application of mupirocin ointment might help break the chain of transmission.…”
mentioning
confidence: 99%
“…Mupirocin calcium ointment is a topical antibiotic indicated for the eradication of nasal carriage of staphylococci, including methicillin-resistant strains. Mupirocin alone or in combination with other antimicrobial agents decreases S. aureus colonization among residents of LTCFs (3,7,8,20). Several outbreaks of methicillin-resistant S. aureus colonization and infection in LTCFs have been reported, and until now, it was thought that the application of mupirocin ointment might help break the chain of transmission.…”
mentioning
confidence: 99%
“…17 Various earlier studies in non-SCI collectives demonstrated the efficacy of rigorous infection control measures to prevent intra-hospital spread of MRSA. 9 In a recent study 18 performed in a country with low MRSA incidence, even eradication of the pathogen has been reported. In Switzerland, where overall low rates of MRSA are still observed, endemic MRSA, present in southern and south-western regions, appears to result from continuous introduction of new strains from surrounding southern countries.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, screening high risk patients for the presence of MRSA followed by implementation of isolation or barrier precautions for those found to be infected or colonized has been shown to be effective in controlling MRSA outbreaks in hospitals and long term care facilities (115)(116)(117)(118)(119), and in reducing nosocomial transmission and overall prevalence in facilities where MRSA is endemic (11,110,(120)(121)(122)(123)(124)(125). Jernigan et al (118,121) reported a 15-fold decrease in transmission of MRSA in a hospital when colonized patients were recognized by a screening program and then cared for with isolation precautions, compared with when isolation precautions were used only in patients recognized to have MRSA from clinical specimens.…”
Section: Screening and Surveillancementioning
confidence: 99%